Pathogenese der Psoriasis vulgaris - Schäkel, Knut; Schön, Michael; Ghoreschi, Kamran (Der Hautarzt, 2016)
Psoriasis is an inflammatory T cell-mediated autoimmune disease of skin and joints that affects 2-4 % of the adult population and 0.1-1 % of children. Genetic susceptibility, environmental triggering factors, and innate immune processes initiate psoriasis pathogenesis that results in an adaptive autoreactive response. The T cell response is orchestrated by CD 8+ T cells in the epidermis and by CD 4+ T cells in the dermis that predominantly produce interleukin-17 (IL‑17). Research of the past 15 years unraveled cellular and molecular mechanisms as well as cytokines like TNF-α or IL‑23 that contribute to psoriatic inflammation. This knowledge has been translated into clinical practice and a number of antipsoriatic small molecules and immunobiologics are now available. Here, we discuss the current principles of psoriasis pathogenesis in the context of modern therapies.
Gesehen am 08.08.2019